Work-life balance and work from home experience: Perceived organizational support and resilience of European workers during COVID-19 - Pedro Ferreira; Sofia Gomes (Administrative Sciences, 2023)
During the COVID-19 pandemic, most workers had to work from home due to the successive lockdowns across European countries. This constraint posed significant challenges to many workers and companies regarding working conditions and work-life balance. Framed by the job demands-resources model (JD-R), the goal of this paper is to examine the association of perceived organizational support (POS) and individual resilience (IR) with work-life balance (WLB) during the COVID-19 pandemic across European countries. This goal is complemented by assessing the role of work-from-home (WFH) as a mediator. Based on a quantitative approach, data were extracted from the second round of the survey "Living, Working, and COVID-19" from Eurofound. A series of regressions using SEM-PLS tested the hypothesis. Findings reveal that WFH negatively influences WLB. POS positively influences WFH and negatively influences WLB when mediated by WFH. IR negatively influences WFH and positively influences WLB when mediated by WFH. These results have essential theoretical implications related to the relations between individual and organizational resources and WLB and practical implications for the management of WFH, namely, the importance of providing adequate organizational resources and promoting the development of individual resources.
Keywords: 350; COVID-19; Europe; perceived organizational support (POS) individual resilience; work-from-home (WFH); work-life balance